SOCIAL COMMERCE IN THE GENERATION Z CONTEXT: THE ROLE OF SOCIAL SUPPORT AND PRIVACY RISK AMONG TIKTOK USERS IN INDONESIA - Tjoa, Nico Jeremy Patrick; Wijayadne, Devi Rahnjen; Wongso, Nikolas (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study focuses on TikTok’s growing influence as a social commerce platform among Generation Z users in Indonesia. It examines the impact of Social Commerce Information Sharing on the formation of Social Support and Trust, as well as their effects on Purchase Intention. The moderating role of Perceived Privacy Risk between Social Support and Trust is also explored. Using a quantitative design with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were gathered from 230 online respondents. Adapted from Tseng et al. (2023), the research model aims to generate both academic contributions and strategic recommendations for enhancing TikTok Shop’s business performance.